Eco-friendly management of the flea beetle, Podagrica species (Coleoptera: Chrysomelidae) on okra (Abelmoschus esculentus (L.) Moench) with Artemisia annua L. seed extract - Frank Onyemaobi Ojiako; Christopher Emeka Ahuchaogu; Samuel Echezona Okere; Brendan Chigozie Nwaokeneme (International Journal of Advances in Applied Sciences, 2023)
Okra, grown and consumed in every ecological zone, is amongst the most sort after fruit vegetable crops in Nigeria. The crop is often infested by diverse field insect pests, especially the flea beetle Podagrica species, which impinges on its growth and productivity. The application of synthetic pesticides has been the generic insect pest control measure due to its touted effectiveness. These synthetics, however, has safety concerns which include; hazard to human health, amplification of toxins in the food chain, pest resurgence, domestic animals and human poisoning, environmental pollution, insect resistance, natural enemies destruction; springs, wells, rivers, and underground water contamination. Stakeholders are advocating an alternative management approach that is sustainable with less negative social and environmental impact. This study, therefore, compared the insecticidal efficacy of Artemisia annua (source of the antimalarial artemisinin) seed extract in comparison with Cypermethrin 10 EC, a synthetic insecticide, in controlling Podagrica species, the major field insect pests of okra. The trial was set out in a 7 x 4 factorial arrangement integrated into a randomized complete block design and replicated thrice. Cypermethrin 10 E.C was tested at 0.25 ml, 0.50 ml, and 0.70 ml/100 ml of water, while Artemisia annua extract was applied at 1.00 ml, 2.00 ml, and 3.00 ml/100 ml of water respectively. The control for both treatments was designated 0.0 ml. Data on leaf damage and flea beetle abundance were carried out from 4-10 weeks after planting (WAP) whilst the pods’ weight was measured at maturity. The result shows that i) the concentrations of Artemisia extract and Cypermethrin sprayed provided comparable protection to okra against the flea beetle; ii) the yield of okra (pod weight) does not vary between Artemisia annua extract and Cypermethrin treated plots; and iii) flea beetle infestations vary with okra developmental stages.